Upaya meningkatkan kompetensi akademik, sosial, dan profesional mahasiswa baru melalui pelatihan etika berkomunikasi verbal dan nonverbal berbasis praktik - Murdia, Murdia; Sudirman, Nurul Ilmi; Budiman, Andi Nurul Annisa (Nur Science Institute, 2025)
Good communication, especially for students, is important for building relationships with lecturers and peers, as it supports the learning process and prepares students for professional demands. This community service aims to enhance the ethical communication skills of new students, with a focus on verbal and nonverbal aspects. This training involved 70 first-semester students from the English Language Education and English Literature programs, class of 2025, at Universitas Negeri Makassar. The methods employed included lectures, discussions, and practical sessions conducted in a seminar format using a participatory approach. The findings indicated several benefits: (1) Academic – Students learned to express opinions politely, logically, and in an organized manner with lecturers; (2) Social – Students developed empathy, tolerance, and respect for differences; (3) Professional – Students increased awareness of campus dress ethics. The main output of this community service program was an ethical guideline for communication with lecturers and educational staff. The training successfully fostered students' ethical communication skills, both verbal and nonverbal.